Evaluasi Pemanfaatan Metode Problem-Based Learning untuk Memotivasi Siswa SMK di Kota Magelang dalam Pembelajaran - Dwi Lathif Kurniawan (Journal of Informatics and Vocational Education, 2022)
Variations in replacing innovative methods in the learning process are needed so that students stay energized in the learning process. This research was conducted at one of the Vocational High Schools in Magelang City by utilizing the Problem-Based Learning (PBL) method to know the amplification of students' learning motivation in learning. This research is a Classroom Action Research (CAR) using four stages, namely First Planning; Second Action; Third Observation, and Fourth Reflection. The sample of this research was ten students of class X at SMK in the city of Magelang, who were determined using a purposive sample technique, namely sampling with a particular purpose. The data collected in this study used observation and interview techniques. The results showed that using Problem-Based Learning learning methods proved effective in amplifying the motivation of SMK students in Magelang City, especially in informatics subjects. Besides that, it can also improve learning outcomes optimally because the learning obtained is more meaningful.